De la Economía Tradicional a la Economía Digital Compartida - Sarmiento Suárez, Jaime Enrique (2017)
The world economy has been undergoing major changes, which have led to the traditional economy based on hyper-consumerism being threatened and displaced by a new economic trend based on intelligent and sustainable consumption, a consumption that is concerned about not using more than what is necessary, consumption based on collaboration and the use of idle goods. This new phenomenon is derived from the economic crisis that the world was facing in the last decade, the heyday of social networks and participatory behavior on the Internet, consolidating a new business strategy that allows reaching more people in a faster and more effective According to estimates the collaborative digital economy for the year 2025, will move 235,000 million dollars. In Latin America, this trend is taking shape up to now, and just as at the global level it is trying to understand and coexist the two approaches, traditional and digital, so that they do not quarrel among themselves, and what is sought is a " healthy "competition that ultimately benefits the end user, for them the countries in the world have the task of seeking the best regulatory frameworks that allow fair competition between the parties. In the case of Colombia, this process is in full embryonic status in terms of laws, and in terms of coexistence since there is no structured legal framework has allowed a series of situations that have led to find the two economic schemes.